This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
its simple
-2x - 12 = -42 -2x = -42 + 12 -2x = -30 2x = 30 x = 30/2 x= 15
(-2x-12=-42) --> add 12 on each side (-2x=-30) --> multiply both sides by -1 (2x=30) --> divide both sides by 2 (x=15)
Given equation.
− 2 x − 1 2 = − 4 2
− 2 x = − 4 2 + 1 2
− 2 x = − 3 0
x = 1 5
Thus, the answer is: x = 1 5
-2x=-42+12;-2x=-30;x=-30/-2=15
Given Equation -2x -12 = -42
Combine like terms: -2x=-42 + 12
Answer: -2x=-30
Eliminate the numerical coefficient: -2x/2=-30/2
Final Answer: x=15
Simplifying -2x + -12 = -42
Reorder the terms: -12 + -2x = -42
Solving -12 + -2x = -42
Move all terms containing x to the left, all other terms to the right.
Add '12' to each side of the equation. -12 + 12 + -2x = -42 + 12
Combine like terms: -12 + 12 = 0 0 + -2x = -42 + 12 -2x = -42 + 12
Combine like terms: -42 + 12 = -30 -2x = -30
Divide each side by '-2'. x = 15
Simplifying x = 15
-2x -12= -42 -2x= -42+ 12 -2x= -30 x= -30/ -2 x= 15
-2x - 12 = -42 -2x = -42 + 12 -2x = -30 2x = 30 x = 30/2 x= 15
Problem Loading...
Note Loading...
Set Loading...
Given equation is -----> − 2 x − 1 2 = − 4 2 . So----
− 2 x − 1 2 = − 4 2
⟹ 2 x = 4 2 − 1 2
⟹ 2 x = 3 0 ⟹ x = 2 3 0 ⟹ x = 1 5